PRAGMATIC STUDY OF INSULTING SPEECH ACTS IN CASES OF DEFAMATION - Butra-Butar, Charles (LUMBUNG AKSARA, 2024)
The research aims to prove that a person's speech acts can be categorized as unlawful. This study includes the text and context of someone's speech. The data for this research comes from the BAP reporting from the Republic of Indonesia Police, South Labuhan Batu Police. The method used in analyzing data is speech events, aspects of speech situations according to Leech. 1. Speakers and addressees (addressers or addressees) Speakers and addressees include speakers and listeners. 2. The context of an utterance. Context is all background knowledge, 3. The goals of an utterance. The results of this research are that it can be proven that the speech acts carried out by the reporting party can be categorized as defaming the reporter or victim using the mode of accusations of lies, incitement and persecution.